Analysis of extreme precipitation indices in the Marche region (central Italy), combined with the assessment of energy implications and hydrogeological risk. (February 2020) - Gentilucci, M.; Barbieri, M.; D'Aprile, F.; Zardi, D.
Abstract: Extreme weather events are increasingly affecting the climate of our planet and they cause natural disasters that are often dangerous to human life. Furthermore, the management of extreme events is very important and can be mitigated by artificial reservoirs, such as those existing in the region. From this point of view, the management of extreme events would become an opportunity for development linked to the production of energy through artificial reservoirs. The aim of this study is to assess the changes of these phenomena, in a small area of central Italy (Marche region), calculating 11 extreme precipitation indices from 1961 to 2017. The analysis shows an extremisation of rain events, with an increase in indices CDD, CWD and R99. However the innovativeness of this research lies in the spatialization of these extreme indices, through areal interpolations performed by GIS software. The territorial assessment of extreme precipitation events has revealed significant local countertrends, useful for hydrogeological protection, water resource management and energy production.